2002
DOI: 10.1016/s1534-5807(02)00126-0
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 Controls Cell Movements during Zebrafish Gastrulation

Abstract: Vertebrate axis formation requires both the correct specification of cell fates and the coordination of gastrulation movements. We report that the zebrafish signal transducer and activator of transcription 3 (Stat3) is activated on the dorsal side by the maternal Wnt/beta-catenin pathway. Zebrafish embryos lacking Stat3 activity display abnormal cell movements during gastrulation, resulting in a mispositioned head and a shortened anterior-posterior axis, but show no defects in early cell fate specification. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 60 publications
8
141
3
1
Order By: Relevance
“…Our recent results show that zebrafish dpr2 functions in regulation of convergence and extension movements during gastrulation (Waxman et al, 2004). Research by Yamashita et al (2002) showed that ␤-catenin signaling somehow increased phosphorylation of Stat3, which regulates proper convergence and extension movements. Thus, ␤-catenin activation of dpr2 constitutes the second known example of ␤-catenin signaling regulating morphogenesis and the first in which regulation is at the level of transcription.…”
Section: Positive Feedback Loops and Cross-regulation Of Signaling Pamentioning
confidence: 77%
See 2 more Smart Citations
“…Our recent results show that zebrafish dpr2 functions in regulation of convergence and extension movements during gastrulation (Waxman et al, 2004). Research by Yamashita et al (2002) showed that ␤-catenin signaling somehow increased phosphorylation of Stat3, which regulates proper convergence and extension movements. Thus, ␤-catenin activation of dpr2 constitutes the second known example of ␤-catenin signaling regulating morphogenesis and the first in which regulation is at the level of transcription.…”
Section: Positive Feedback Loops and Cross-regulation Of Signaling Pamentioning
confidence: 77%
“…The accumulation of ␤-catenin on the future dorsal side leads to the expression of genes of the dorsal organizer and, in at least one case, potentiation of the action of an organizer protein (Kelly et al, 2000;Ryu et al, 2001;Solnica-Krezel and Driever, 2001;Yamashita et al, 2002;Dougan et al, 2003). Organizer genes promote dorsal axis formation in three important ways: by antagonizing the activity of ventralizing genes, by establishing dorsal mesendoderm, and by promoting proper gastrulation movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 has been shown to be required for cell motility in a few other contexts. Essential role of STAT3 was shown in epithelial to mesenchymal transition during zebrafish embryo gastrulation (Yamashita et al, 2002). STAT3-deficient keratinocytes showed increased cell adhesiveness and compromised growth factor-inducible cell migration, accompanying with an increased hyperphosphorylation of focal adhesion and its component protein p130cas (Kira et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Stat3 pathway is activated in the gastrula organizer where it is thought to set up a signaling center that attracts lateral cells and thus promotes convergence toward the dorsal midline. Moreover, function of Stat3 is required in axial mesoderm cells for their anterior migration to drive extension (Yamashita et al, 2002Miyagi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%